2015
DOI: 10.1111/apha.12477
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 activates autonomic and behavioural warmth‐defence responses in Wistar rats

Abstract: Our results suggest, for the first time, that TRPV4 channel is involved in the recruitment of behavioural and autonomic warmth-defence responses to regulate core body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 54 publications
1
45
1
Order By: Relevance
“…Surely, they are no atavism because several functions of these receptors could be identified, for example regulation of barrier homoeostasis. Nevertheless, the broad function spectrum of these ectopic receptors is only marginally analysed to date . According to these results, also more ectopically expressed human ORs have been identified, and the functionality of ORs in non‐olfactory cell types has become better understood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surely, they are no atavism because several functions of these receptors could be identified, for example regulation of barrier homoeostasis. Nevertheless, the broad function spectrum of these ectopic receptors is only marginally analysed to date . According to these results, also more ectopically expressed human ORs have been identified, and the functionality of ORs in non‐olfactory cell types has become better understood .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, also a wide range of classic central nervous system (CNS) neuroreceptors, which are usually necessary for auditory and visual functions, could be found in the skin, such as opsin receptors and transient receptor potential channels. They seem to play an important role, for example, in permeability barrier homoeostasis, but their full function is also still under investigation …”
Section: Introductionmentioning
confidence: 99%
“…To infer the putative consequences of woolly mammothspecific amino acid substitutions in thermoTRPs, we generated structural models of the ancestral Asian elephant/mammoth (AncGajah; Figure 1A) and ancestral mammoth (AncMammoth; Figure 1A) TRPA1, which mediates nocifensive (Karashima et al, 2009;Kwan et al, 2006;Vizin et al, 2015) and vascular responses to noxious cold (Aubdool et al, 2014) as well as generally potentiating responses to noxious stimuli (del Camino et al, 2010), and TRPV4, which mediates autonomic and behavioral responses to cold (Vizin et al, 2015). We found that the elephantid TRPA1 and TRPV4 proteins were predicted to adopt the common TRP channel structure, which is composed of a series of amino terminal ankyrin repeats (ARD), separated by a membrane proximal domain (MPD) from the six transmembrane helices (S1-S6) that form the ion-permeable pore in tetrameric channels ( Figure 4B).…”
Section: Substitutions In Temperature-sensitive Transient Receptor Pomentioning
confidence: 99%
“…The lack of such a direct confirmation is the major shortcoming of the Vizin et al . () study, as it leaves the door open for the possibility of an off‐target action, especially in view of the contradictory and largely negative results of the earlier studies discussed above (Liedtke & Friedman , Lee et al . , Huang et al .…”
mentioning
confidence: 90%
“…In the current issue of Acta Physiologica , Vizin et al . () report the results of a study aimed at establishing whether another TRP channel, vanilloid‐4 (V4), plays a similarly critical role in heat defences.…”
mentioning
confidence: 99%